2019
DOI: 10.3390/antiox8100465
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, NF-κB-Mediated Inflammation and Apoptosis in the Testes of Streptozotocin–Induced Diabetic Rats: Combined Protective Effects of Malaysian Propolis and Metformin

Abstract: Oxidative stress, inflammation and apoptosis are major complications that trigger organ failure in diabetes mellitus (DM), and are proven to adversely affect the male reproductive system. Clinical and experimental studies have demonstrated the promising protective effects of propolis in DM and its associated systemic effects. Herein, we investigated the effect of Malaysian propolis (MP) on testicular oxidative stress, inflammation and apoptosis in diabetic rats. Further, the possibility of a complementary effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
76
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 74 publications
16
76
0
4
Order By: Relevance
“…Caspase-3, a sort of cysteine protease, is an important mediator of apoptosis. Many reports have indicated that caspase-3 is upregulated in diabetic conditions [54]. In this study, we show that there was an association between diabetic sexual dysfunction and caspase-3 expression, as evidenced by apparent downregulation of caspase-3 content in the germ cells of D+MC-treated rats, suggesting that inhibition of caspase-3 activity may be one of the mechanisms by which MC protects against diabetic testicular injury.…”
Section: Discussionsupporting
confidence: 62%
“…Caspase-3, a sort of cysteine protease, is an important mediator of apoptosis. Many reports have indicated that caspase-3 is upregulated in diabetic conditions [54]. In this study, we show that there was an association between diabetic sexual dysfunction and caspase-3 expression, as evidenced by apparent downregulation of caspase-3 content in the germ cells of D+MC-treated rats, suggesting that inhibition of caspase-3 activity may be one of the mechanisms by which MC protects against diabetic testicular injury.…”
Section: Discussionsupporting
confidence: 62%
“…The presence of pinocembrin (1), chrysin (2), galangin (3), ferulic acid (10), syringic acid (11), and caffeic acid (12) suggest that its main botanical source are a species of Populus typical of the country, such as Populus mexicana Wesmael, Populus guzmanantlensis Vazques and Cuevas and Populus simaroa Rzedowski. Although flavonoids without B-ring substituents appear common in temperate propolis from both the northern and southern hemispheres, in this study we report for the first time the presence of dillenetin (6) and isorhamnetin (7) with B-ring substitution as constituents of Mexican poplar propolis. To the best of our knowledge, this is the first report of dillenetin (6) as a propolis constituent.…”
Section: Chemical Composition Of Eep Gua-4mentioning
confidence: 58%
“…The EtOH-soluble extract of sample GUA-4 was fractionated by chromatography on a VLC column and by Sephadex LH-20, giving 12 known compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The compounds were identified as pinocembrin (1, 405.4 mg) [33], chrysin (2, 126.3 mg) [34], galangin (3, 56.7 mg) [33], alpinetin (4, 15.6 mg) [35], 5-methyl-pinobanksin ether (5, 16.8 mg) [36], dillenetin (6, 12.3 mg) [37], isorhamnetin (7, 24.6 mg) [38], 5-methylgalangin ether (8, 9.8 mg) [39], 5-methylchrysin ether (9, 16.3 mg) [40], ferulic acid (10, 24.9 mg) [33], syringic acid (11, 6.7 mg), and caffeic acid (12, 8.9 mg) [33] ( Figure S1) by means of 1D (Table S1) and 2D NMR spectral analysis.…”
Section: Chemical Composition Of Eep Gua-4mentioning
confidence: 99%
“…[23][24][25] Our group reported significant antioxidant, anti-inflammatory and anti-apoptotic effects of Malaysian propolis (MP) in the pancreas, liver, testes and epididymis of diabetic rats. 22,26,27 In the present study, therefore, we report for the first time, the effect of propolis on steroidogenesis, spermatogenesis, testicular lactate transport, sexual behaviour and fertility outcome in diabetic rats. Following our previously reported better blood glucose modulation in diabetic rats treated with MP + metformin combination relative to MP and metformin monotherapies, 22 we report the effect of this alliance on the above-mentioned reproductive function parameters in order to explore the benefits of the combination in the event that neither of the two therapies is able to significantly reverse these negative effects.…”
Section: Introductionmentioning
confidence: 60%
“…Intra-testicular oxidative stress, inflammation and germ cell apoptosis, which occur as a result of hyperglycaemia-induced overproduction of ROS, are implicated in DM-induced fertility decline. 27,34 We reported that these ROS-associated effects were significantly suppressed by MP, Met and MP + Met, with the best outcome following intervention with the combined therapy. 27 In the present study, therefore, we explored the benefits of these interventions on other indispensable target processes in the testes (steroidogenesis, lactate metabolism and spermatogenesis) which are required for male fertility, in addition to a post-testicular event, sexual behaviour.…”
Section: Discussionmentioning
confidence: 97%